(untitled) - Haug, Eberhard (Singapore, 2004)
This book deals with the theory and experiment of the elementary process of bremsstrahlung, where photons are detected in coincidence with decelerated outgoing electrons. Such experiments allow for a more stringent check of the theoretical work. The main emphasis is laid on electron-atom bremsstrahlung and electron-electron bremsstrahlung, but further bremsstrahlung processes are also dealt with. In the theoretical parts, triply differential cross sections are derived in various approximations, including electron spin and photon-polarization. In the experimental sections, electron-photon coincidence experiments are discussed. These are done partly with transversely polarized electron beams and partly with detectors for the bremsstrahlung linear polarization.
Keywords: Bức xạ hãm,Bremsstrahlung